Problems and Solutions of Preventing Children Exploitation Tourism A Case study of Samut Songkhram - Tipcharoen, Sirinan (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
This reseacrh represents the results of the investigation regarding the problems and solutions of preventing children exploitation tourism. Data collection has been done through quantitative research where samples are from several groups. Theses samples consist of business owners, volunteers and tourists. The study examines the area of Samut Songkhram, a province in Thailand. Questionnaire was used as a research instrument for data gathering. Tourists were the majority of the study samples. There was no fixed amount of the samples. Overalls, there were approximately 300 samples. Statistical analysis has been done in order to identify the Arithmetic Mean, the Standard Deviation (SD) and Pearson Product Moment Correlation Coefficient. The results of the study reveal that the correlation between prevention of children exploitation tourism is found to be less. This has been reported with statistic figure at .05. This means that prevention, problem solutions and the investigation of the influence factors were not relevant to prevent children exploitation tourism. Article history : Received 14 July 2019 Revised 31 January 2020 Accepted 2 February 2020 SIMILARITY INDEX = 0.00 %